Snake, Spell, Spirit, and Soteriology: The Birth of an Indian God Jiedi 揭諦 in Middle-Period China (618–1279) - Zhaohua Yang (Religions, 2023)
I introduce a Buddhist god named Jiedi, believed to be a personification of the renowned gate mantra in the Heart Sūtra. I argue for a complex genesis story where the transference of the nāga-taming function and aquatic setting from the rainmaking spell in the Great Cloud Sūtra to the Heart Sūtra Mantra, coupled with its exegetical tradition emphasizing the soteriological metaphor of crossing, created an independent cult of the Jiedi Mantra. In battling chthonic snake spirits demanding virgin sacrifice in Sichuan, a regional variation of a cosmopolitan alchemical theme, the mantra was personified into a god associated with water and warfare. The exorcistic function of the mantra was the motor behind its apotheosis in Middle-period China. While he was elevated from a mere spirit to a vidyārāja (“wisdom king”) in tantric Buddhism, his cult was also disseminated in the Song, witnessing him provide broad deliverance in diverse areas such as industry, agriculture, infrastructure, military, and civil service. In late imperial China, he further imprinted himself on sacred geography, became a special class of warrior god, made inroads into Daoism and local religion, and proliferated in vernacular fiction and drama. An exotic Indian god was born on Chinese soil.